Using growth kinetics to evaluate the stress factors faced by Salmonella Typhimurium during survival on meat - Rodriguez C., Karoll E. (Zamorano: Escuela Agrícola Panamericana, 2025)
The poultry sector, a major source of animal protein worldwide, confronts serious food safety and contamination issues. Where Salmonella is the most common pathogen. This study looks at the growth kinetics of different genetic variants of Salmonella enterica serovar Typhimurium to see whether stressors affect their survival in chicken meat. Nine strains, including the wild-type ST4/74, and eight isogenic deletion mutants (?fur, ?rpoE, ?dam, ?hilD, ?ssrB, ?fnr, ?slyA, and ?entC), were investigated for their growth kinetics in chicken meat during a 16-hour period. A Complete Randomized Design was used in this study, where the control was ST4/74. A Student's t-test was performed to determine statistical significance (P < 0.05). Except for the ?fur mutant, all other strains displayed identical growth kinetics to the wild-type. This suggests that the assessed genes, excluding fur, are not required for Salmonella's survival in chicken meat under this study conditions. The ?fur mutant exhibited substantial inhibition due to intracellular iron toxicity. Treatment with the iron chelator bipyridine alleviated this effect. These findings highlight the fur gene's critical function in regulating iron homeostasis, which helps Salmonella survive in chicken meat. Insights into the amount of iron as a stress factor in chicken meat were established when ST4/74 was treated with bipyridyl. Understanding these genetic underpinnings provides a better insight into the molecular biological behavior in this food matrix.